Stacking up: a new approach for cell culture studies - Diosangeles Soto Veliz; Hongbo Zhang; Martti Toivakka (ROYAL SOC CHEMISTRY, 2025)
Traditional cell culture relies mostly on flat plastic surfaces, such as Petri dishes and multiwell plates. These commercial surfaces provide limited flexibility for experimental design. In contrast, cell biology increasingly demands surface customisation, functionalisation, and cell monitoring in order to obtain data that is relevant in vivo. The development of research areas such as microfluidics and electrochemical detection methods greatly promoted the customised design of cell culture platforms. However, the challenges for mass production and material limitations prevent their widespread usage and commercialisation. This article presents a new cell culture platform based on stacks of a transparent flexible printable substrate. The arrangement introduces multi-layered stacks for possible manipulation and access to the cells. The platform is highly compatible with current technologies, such as colorimetric imaging and fluorescence microscopy. In addition, it can potentially integrate, e.g., biomaterials, patterning, microfluidics, electrochemical detection and other techniques to influence, monitor, and assess cell behaviour in a multitude of different settings. More importantly, the platform is a low-cost alternative customisable through functional printing and coating technologies. The device shown in this manuscript represents a prototype for more sophisticated variations that will expand the relevance of in vitro studies in cell biology.